2022
DOI: 10.1021/acs.analchem.2c02875
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Identifying Exposed-over-Unexposed C–C+ Pairs in Human Telomeric i-Motif Structures with Length-Dependent Polymorphism

Abstract: The i-motif structure (iM) has attracted much attention, because of its in vivo bioactivity and wide in vitro applications such as DNA-based switches. Herein, the length-dependent folding of cytosine-rich repeats of the human telomeric 5′-(CCCTAA)n‑1CCC-3′ (iM-n, where n = 2–8) was fully explored. We found that iM-4, iM-5, and iM-8 mainly form the intramolecular monomer iM structures, while a tetramolecular structure populates only for iM-3. However, iM-6 and iM-7 have the potential to fold as well into the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Although we were able to identify the best conditions for iMab to recognize its target, we still observed a clear WB band for the hTeloC 3×2 and 3×3 sequences, which, based on their sequence, would not form intramolecular iM structures. However, we reasoned that both oligonucleotides could form intermolecular iM structures (25), which would explain their binding to iMab. Multimolecular iMs have mainly been studied for their application in nanotechnology and it is generally reported that they form in sequences with short C-tracts (25, 26), and therefore show lower stability than intramolecular structures (27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we were able to identify the best conditions for iMab to recognize its target, we still observed a clear WB band for the hTeloC 3×2 and 3×3 sequences, which, based on their sequence, would not form intramolecular iM structures. However, we reasoned that both oligonucleotides could form intermolecular iM structures (25), which would explain their binding to iMab. Multimolecular iMs have mainly been studied for their application in nanotechnology and it is generally reported that they form in sequences with short C-tracts (25, 26), and therefore show lower stability than intramolecular structures (27).…”
Section: Resultsmentioning
confidence: 99%
“…However, we reasoned that both oligonucleotides could form intermolecular iM structures (25), which would explain their binding to iMab. Multimolecular iMs have mainly been studied for their application in nanotechnology and it is generally reported that they form in sequences with short C-tracts (25, 26), and therefore show lower stability than intramolecular structures (27). To prove our hypothesis, we performed 1 H NMR analysis at two different oligonucleotide concentrations (Figure 3A), since higher DNA concentrations stimulate the formation of intermolecular structures (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation